Hubungan Pendidikan Kesehatan Dengan Media Booklet Asik Biru (Ayo Sukseskan Asi Eksklusif Bagi Ibu Baru) Terhadap Pengetahuan Ibu Hamil Tentang ASI Eksklusif Di Wilayah Kerja Puskesmas Ngesrep Kota Semarang - Puji Hastuti; Ninda Nurjanah; Yanik Muyassaroh (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Exclusive breastfeeding is breastfeeding for infants aged 0-6 months without additional food. Data for 2022 in the working area of the Ngesrep health center in Semarang City in September has not reached the target. The purpose of this study is to determine the relationship between health education and ASIK BIRU booklet media on pregnant women's knowledge about exclusive breastfeeding. The research was conducted in the working area of the Ngesrep Health Center in Semarang City. The method used is quasy experimental with one group pre test and post test design. The samples in the study were selected using purposive sampling techniques, and data collection was carried out using questionnaire instruments. The results showed that there was a relationship of health education with ASIK BIRU booklet media on the level of knowledge of pregnant women about exclusive breastfeeding with a p-value of 0.001<0.05. It is hoped that health workers at Community Health Center can use the ASIK BIRU booklet as a media in providing health education and can be used as a handbook for pregnant women to prepare for the presence of their babies.